\(In vitro\) regeneration and acclimatization of \(Anthurium scherzerianum \)schott plants - Van Khiem, Dinh; Xuan Huyen, Phan; Thanh Hang, Nguyen Thi; Phuong Hoang, Nguyen Thi (Academia Journal of Biology, 2022)
This study investigated the effects of different PGRs on in vitro plant regeneration of Anthurium scherzerianum Schott and acclimatization in the ex vitro stage. Depending on the objective of each experiment, the in vitro shoots were induced from callus cultured on a modified Murashige and Skoog (MS) medium containing cytokinins and auxins. Results showed that 90% of leaf explants and 48% of petiole explants produced callus. A half-strength MS medium supplemented with 1.0 mg/l Kinetin (KIN) gave the best result for shoot regeneration and 1.5 mg/l α-naphthalene acetic acid (NAA) is suitable for rooting of A. scherzerianum. The culture vessel having a hole on the cap gave the best result on the growth of A. scherzerianum plantlets. After 90 days transferred to the greenhouse, in vitro plantlets which were cultivated on a mixed substrate of coconut fiber powder: rice husk ash: compost (6:3:1, respectively) had a better growth (shoot length of 8.88 cm, root length of 3.44 cm) than those on another mixed substrate of coconut fiber powder: compost (9:1, respectively).